L’utilisation du manuel Chouette dans l’enseignement de la prononciation du français auprès des élèves de première année SMA N 2 Kudus - Rike Destiawati; Aisyiah Al Adawiyah (Universitas Negeri Semarang, 2026)
French, as a foreign language, remains a challenge for many students in Indonesia, particularly regarding pronunciation, which differs significantly from Indonesian. This is why it is important to have a suitable method and teaching materials to help students learn French sounds. The aim of this research is to describe the use of the textbook *Chouette: Syllabic Reading Method in teaching French pronunciation to Year 11 pupils at SMA Negeri 2 Kudus. This study employs a qualitative approach and a descriptive method. Data were collected through observations, interviews, and documents. The results show that the Chouette textbook is effective in helping pupils understand French sounds through a progressive syllabic and visual method. The teacher's strategy consists of imitation and repetition, with both group and individual exercises. However, differences were observed between the planned strategy and its implementation in practice. Some classes showed good student participation, whilst others remained passive. The assessment shows that most pupils made progress in pronunciation, even though the audio and individual exercises are not yet used regularly. This study concludes that the Chouette book makes a positive contribution to pronunciation learning, but its effectiveness depends heavily on the teacher’s strategy and the regularity of its use.